DETERMINANT INFLATION ON MURABAHAH FINANCING IN SHARIA BANKS IN INDONESIA 2015-2019 - Erick S Yahya; Supandi Rahman (Department of Islamic Banking, Faculty of Islamic Economics and Business, IAIN Sultan Amai Gorontalo, 2021)
This study aims to know the effect of inflation on Murabahah (sale-purchase agrrement between the bank and the customer with known profit) financing in Sharia banks in Indonesia. The data in this study are secondary data from the official website of each Sharia bank and then analyzed by using simple regression analysis. The finding shows that the inflation rate has a positive and significant effect on Murabahah financing in Sharia banks in Indonesia. The positive coefficient indicates that an increase in inflation will make people greatly desire to apply for Murabahah financing because they are worried about a greater increase in inflation in the following year. This aldo occurs because the increase in inflation makes people save a lot in Sharia banks, so that banks must optimally use these funds in the form of financing operations of what is called Murabaha financing. The coefficient of determination is 0.9871, meaning that 98.71% of Murabahah financing in Sharia banks in Indonesia is explained by the inflation rate. Meanwhile, 1.29% is the variability of other variables on Murabahah financing, such as banking profit variables, CAR ratios, NPF ratios, and third party funds.